On-off switch of charge-separated states of pyridine-vinylene-linked porphyrin-C-60 conjugates detected by EPR - Kirner, Sabrina; Arteaga, Danny; Henkel, Christian; Margrat, Johannes T.; Alegret, Nuria; Ohkubo, Kei; Insuasty, Braulio; Ortiz, Alejandro; Martin, Nazario; Echegoyen, Luis; Fukuzumi, Shunichi; Clark, Timothy; et al. (Chemical Science, 2015)
The design, synthesis, and electronic properties of a new series of D-pi-A conjugates consisting of free base (H2P) and zinc porphyrins (ZnP) as electron donors and a fullerene (C-60) as electron acceptor, in which the two electroactive entities are covalently linked through pyridine-vinylene spacers of different lengths, are described. Electronic interactions in the ground state were characterized by electrochemical and absorption measurements, which were further supported with theoretical calculations. Most importantly, charge-transfer bands were observed in the absorption spectra, indicating a strong push-pull behavior. In the excited states, electronic interactions were detected by selective photoexcitation under steady-state conditions, by time-resolved fluorescence investigations, and by pump probe experiments on the femto-, pico-, and nanosecond time scales. Porphyrin fluorescence is quenched for the different D-pi-A conjugates, from which we conclude that the deactivation mechanisms of the excited singlet states are based on photoinduced energy-and/or electron transfer processes between H2P/ZnP and C-60, mediated through the molecular spacers. The fluorescence intensity decreases and the fluorescence lifetimes shorten as the spacer length decreases and as the spacer substitution changes. With the help of transient absorption spectroscopy, the formation of charge-separated states involving oxidized H2P/ZnP and reduced C-60 was confirmed. Lifetimes of the corresponding charge-separated states, which ranged from similar to 400 picoseconds to 165 nanoseconds, depend on the spacer length, the spacer substitution, and the solvent polarity. Interestingly, D-pi-A conjugates containing the longest linkers did not necessarily exhibit the longest charge-separated state lifetimes. The distances between the electron donors and the acceptors were calculated by molecular modelling. The longest charge-separated state lifetime corresponded to the D-p-A conjugate with the longest electron donor-acceptor distance. Likewise, EPR measurements in frozen media revealed charge separated states in all the D-p-A conjugates investigated. A sharp peak with g values similar to 2.000 was assigned to reduced C-60, while a broader, less intense signal (g similar to 2.003) was assigned to oxidized H2P/ZnP. On-off switching of the formation and decay of the charge-separated states was detected by EPR at 77 K by repeatedly turning the irradiation source on and off.